Arboreal vegetation of deciduous lower rainforest in degraded litosol and eutric regosol soils - Ortega-Baranda, Verónica; Sánchez-Bernal, Edgar Iván; Sánchez-Aragón, Liliana; Luis-Reyna, María de los Ángeles; Ruvalcaba-Gómez, Gabriel (REVISTA TERRA LATINOAMERICANA, 2020)
In Mexico, low deciduous forests (SBC) are disturbed by agricultural activities. Its regeneration causes the reestablishment of secondary arboreal vegetation with less plant cover and root rooted to the ground produce thermophilic and hydrophobic soils vulnerable to erosion, which prevents the regeneration of SBC. The structure, composition and diversity of the arboreal vegetation in two SBCn degraded lithosols and regosols were determined in two conservation areas located the first in the municipality of San Pedro Mixtepec (SBC-M) and the second in San Pedro Pochutla (SBC-P) of the coast of Oaxaca. In each area, four sampling units of 0.25 ha were established, divided into 25 squares of 100 m² each, in which arboreal individuals with a normal diameter > 2.5 cm were measured. The composition of species, the vertical (height) and horizontal (diameter) structure, the Importance Value Index (IVI) and Forest Value (IVF) were determined. The registered wealth was evaluated by parametric and non-parametric estimators (Chao2), the Simpson indexes (1-Dp) modified by Pielou, Shannon-Weaver (H’), equity (JH’), dominance and similarity (IS). between SBC. Soil samples from the SBC-M were collected and physical-chemical characterization was carried out. The results indicate that the species richness between development conditions (SBC-M = 33; SBC-P = 47) had significant differences (P < 0.05). The vertical structure was between 1 - 10 m and the horizontal one remained in the diameter class 5 (2.5 - 7.5 cm), for both conditions. The species with the highest IVI and IVF were: Ceiba parvifolia, Heliocarpus donnell smithii, Dalbergia congestiflora and Amphipterygium adstringens. The SBC-M and SBC-P had an index I-Dp = 0.911 and 0.919 for H’ = 2.73 and 3.00, in both JH’ = 0.78; the dominance was from 0.157 to 0.219. The similarity of species among forests was 60%.